Evaluation of Hypertension Surveillance Implementation at Padang Bulan Community Health Center - Rapael Giniting; Santy Deasy Siregar; Irma Yanti (PT Publikasiku Academic Solution, 2025)
Hypertension is one of the most prevalent noncommunicable diseases (NCDs) among populations both nationally and internationally. Therefore, surveillance officers play a crucial role in the prevention and control of hypertension. This study aims to evaluate the effectiveness of hypertension surveillance implementation at the Padang Bulan Community Health Center using surveillance attributes. These attributes are used to assess the hypertension surveillance system based on its components. This study employs a qualitative approach. Data collection was conducted through in-depth interviews with surveillance officers, document review, and observation. The results of this study indicate that hypertension surveillance at the Padang Bulan Community Health Center is carried out through the Non-Communicable Disease Monitoring Post (Posbindu PTM) and has been implemented quite well in terms of input, process, and output components. However, there are still challenges, such as errors in the application system or poor internet connection, insufficient time for staff to enter data, and low community interest in checking their health at both the Posbindu PTM and health facilities. The discussion of the research results indicates that surveillance staff need to approach the community to increase public trust in health workers, so that the community is more willing to visit health facilities or the PTM Posbindu to check their health conditions.